Associations between proximity to livestock farms, primary health care visits and self-reported symptoms. Issue 1 (December 2016) - van Dijk, Christel; Smit, Lidwien; Hooiveld, Mariette; Zock, Jan-Paul; Wouters, Inge; Heederik, Dick; Yzermans, C.
Abstract Background Living in a neighbourhood with a high density of livestock farms has been associated with adverse respiratory health effects, but less is known about healthcare utilisation. This study aimed at investigating the associations between livestock exposure and primary health care visits and self-reported symptoms. In addition, we examined the potentially confounding effect of distance from home to general practice. Methods Contact data between 2006 and 2009 were obtained from electronic medical records of 54, 777 persons registered within 16 general practices in an area with a high density of livestock farms in the Netherlands. Data on self-reported symptoms were used from a cross-sectional sample of 531 patients in 2010. Livestock presence in a 500 m radius from home was computed using Geographic Information System data. Results In general, livestock exposure was associated with fewer contacts and self-reported symptoms for respiratory and other conditions. The number of poultry within 500 m was positively associated with the number of contacts. A longer distance to general practice was associated with fewer contacts, but did not confound associations. Conclusions People living close to livestock farms less often see their general practitioner and report symptoms.